Pelatihan Penyusunan Laporan Keuangan kepada Pelaku UKM di Rumah BUMN Sumsel - Mutiara Kemala Ratu; Emilda Emilda; Vhika Meiriasari; Okky Savira (Abdimas Universal, 2024)
Financial Statement Preparation Training is one of the important materials in supporting financial literacy knowledge and improving the ability to prepare financial statements especially by those who act as SMEs. The need of financial reports is to facilitate decision making in the sustainability of their business even if needed also for business tax reporting. This training activity was carried out with partners of Rumah BUMN Sumsel and several SMEs in Palembang who became participants. The participants of this training activity will be given a pre-test and post-test on the preparation of financial statements as a form of evaluation of the sustainability of the training. The results of the training showed that on average there was a significant increase of 60.9% in the ability of the participants. This result shows that the training on financial statement preparation is well received and applied by the participants who act as SMEs.